The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1099/mic.0.000109
|View full text |Cite
|
Sign up to set email alerts
|

PerR controls oxidative stress defence and aerotolerance but not motility-associated phenotypes of Campylobacter jejuni

Abstract: The foodborne bacterial pathogen Campylobacter jejuni is an obligate microaerophile that is exposed to atmospheric oxygen during transmission through the food chain. Survival under aerobic conditions requires the concerted control of oxidative stress systems, which in C. jejuni are intimately connected with iron metabolism via the PerR and Fur regulatory proteins. Here, we have characterized the roles of C. jejuni PerR in oxidative stress and motility phenotypes, and its regulon at the level of transcription, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 62 publications
0
34
0
Order By: Relevance
“…Interestingly, C. jejuni, a Gram-negative bacterium, lacks OxyR and instead possesses the metalloregulator PerR, which is normally found in Gram-positive bacteria such as B. subtilis (26), Staphylococcus aureus (27), Enterococcus faecalis (28), and Streptococcus pyogenes (29). Although the insertional inactivation of PerR has been linked to increased aerotolerance and hyperresistance to H 2 O 2 in C. jejuni (10,12,30), spontaneous mutations conferring peroxide resistance in Campylobacter have not been described. In this study, the MutY mutation in the mutator isolate CMT was found to increase the spontaneous mutation frequency in perR, leading to malfunction of PerR, derepression of the PerR regulon, and consequently the increased emergence of OX R mutants in Campylobacter.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Interestingly, C. jejuni, a Gram-negative bacterium, lacks OxyR and instead possesses the metalloregulator PerR, which is normally found in Gram-positive bacteria such as B. subtilis (26), Staphylococcus aureus (27), Enterococcus faecalis (28), and Streptococcus pyogenes (29). Although the insertional inactivation of PerR has been linked to increased aerotolerance and hyperresistance to H 2 O 2 in C. jejuni (10,12,30), spontaneous mutations conferring peroxide resistance in Campylobacter have not been described. In this study, the MutY mutation in the mutator isolate CMT was found to increase the spontaneous mutation frequency in perR, leading to malfunction of PerR, derepression of the PerR regulon, and consequently the increased emergence of OX R mutants in Campylobacter.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies showed that C. jejuni perR mutants displayed significantly increased peroxide resistance and aerotolerance (10,12,30). For example, there were 2 to 3 log more surviving C. jejuni perR insertional mutants than there were wild-type cells after 9 h of incubation under aerobic conditions (30). Recently, aerotolerant C. jejuni and Campylobacter coli have been increasingly isolated from various sources, including chicken or retail meat samples (34-36).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations